2017
DOI: 10.1007/s12095-017-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of de Bruijn sequences from product of two irreducible polynomials

Abstract: We study a class of Linear Feedback Shift Registers (LFSRs) with characteristic polynomial f (x) = p(x)q(x) where p(x) and q(x) are distinct irreducible polynomials in F 2 [x]. Important properties of the LFSRs, such as the cycle structure and the adjacency graph, are derived. A method to determine a state belonging to each cycle and a generic algorithm to find all conjugate pairs shared by any pair of cycles are given. The process explicitly determines the edges and their labels in the adjacency graph. The re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…If 1 ∈ E 1 ∩ E 2 , i.e., a 1 = a ′ 1 = 1, then there is no conjugate pair between the corresponding pairs of cycles since n 1 = 1, making 2 n 1 − 2 = 0. Keeping p 1 (x) = x + 1, we prove a result that generalizes [7,Prop. 10].…”
Section: Properties Of the Adjacency Graph Of ω ( F (X))mentioning
confidence: 75%
See 2 more Smart Citations
“…If 1 ∈ E 1 ∩ E 2 , i.e., a 1 = a ′ 1 = 1, then there is no conjugate pair between the corresponding pairs of cycles since n 1 = 1, making 2 n 1 − 2 = 0. Keeping p 1 (x) = x + 1, we prove a result that generalizes [7,Prop. 10].…”
Section: Properties Of the Adjacency Graph Of ω ( F (X))mentioning
confidence: 75%
“…We put forward a construction from LFSRs whose characteristic polynomials are products of two distinct irreducible polynomials and showed that it generates a large number of de Bruijn sequences in [7]. In another work [6], whose preliminary results were presented at SETA 2016, we discussed in detail how to determine the cycle structure and find a state for each cycle for an arbitrary polynomial f (x) ∈ F q [x] for any prime power q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3. Concatenated sequences are widely used in wireless communication as these sequences are derived from two PPs, having similar cross correlation and auto-correlations properties to those of the Gold codes and of long PN-sequences [45][46][47][48][49]. A pair of m-sequence generators are used for generating the concatenated sequence by XORing or performing modulo-2 addition of the appropriately shifted versions of the two m-sequences created by two different PPs having the length of 2 R − 1 and 2 S − 1 respectively, 3 Please note that c i over here will be feed to the channel when exploit the RSSE scheme of [18] and [20] to obtain synchronization for m-sequence.…”
Section: B Concatenated Sequencesmentioning
confidence: 99%
“…This applies also for the last and first words in the ordering. DB sequences admit applications in various fields including cryptography [3,4,13,39,43], electrical engineering (mainly since they correspond to feedback-shift-registers) [7,10,11,30,31,32,36], molecular biology [33], and neuroscience [1], to name a few.…”
Section: Introductionmentioning
confidence: 99%